The formation of oriented barium carbonate from the decomposition of yttria-doped barium zirconate films. (September 2020) - Jennings, D.; Ricote, S.; Santiso, J.; Reimanis, I.
Abstract: Yttria doped barium zirconate (BZY) thin films show promise thanks to their high proton conductivities and their possibility for use in studying fundamental processes such as exsolution. This work demonstrates that highly oriented BZY thin (45 nm) films on (100) single crystal strontium titanate decompose into oriented barium carbonate rods and yttria stabilized zirconia when exposed to industrial grade Ar or pure CO2 at 800 °C. It is shown with transmission electron microscopy that the rods nucleate on the BZY surface. The causes and modes of decomposition in these thin films are discussed in detail. Graphical abstract: Image, graphical abstract